Врожайність насіння томату залежно від передпосівної обробки - Shapko, Maryna; Shevchenko, Nadiia; Kovalenko, Galyna; Kuts, Oleksandr (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):305